Reaction process and temperature-resistant properties of B/KNO3/PVDF composites using thermal analysis - Chenyang Li; Minjie Li; Haoyu Song; Xuan Zhan; Chuanhao Xu; Baoyun Ye; Jingyu Wang; Chongwei An (Case Studies in Thermal Engineering, 2024)
Using thermal analysis techniques to explore the relation between temperature and physical and chemical changes in materials is crucial for studying the reaction processes of energetic materials. Herein, thermogravimetry–mass spectrometry was used to study the reaction process of B/KNO3/polyvinylidene fluoride (PVDF) composites. The effects of different PVDF and B contents on the decomposition process, pressure release properties and heat of combustion of the composites were investigated. Furthermore, the thermodynamic and kinetic responses of the composites in a linear integrated state after stimulation at different temperatures were studied. The results show that the addition of PVDF lowered the temperature at which KNO3 decomposed and released [O], enabling the composite to react at a lower temperature. Although the initial reaction temperature increased with increasing PVDF content, excessive PVDF hindered the heat and mass transfer between particles, thereby deteriorating the pressure release characteristics and heat of combustion of the composite. In addition, the B/KNO3/PVDF composites were chemically stabilized by heating at 60 °C for 90 d or at 150 °C for 2 h. This treatment ensured stable combustion and pressure release of the composites. These results provide a reference for studying the reactivity and functional applications of B/KNO3 composites.